Ultralow‐Power Machine Vision with Self‐Powered Sensor Reservoir - Jie Lao; Mengge Yan; Bobo Tian; Chunli Jiang; Chunhua Luo; Zhuozhuang Xie; Qiuxiang Zhu; Zhiqiang Bao; Ni Zhong; Xiaodong Tang; Linfeng Sun; Guangjian Wu; et al. (Advanced Science, 2022)
Abstract A neuromorphic visual system integrating optoelectronic synapses to perform the in‐sensor computing is triggering a revolution due to the reduction of latency and energy consumption. Here it is demonstrated that the dwell time of photon‐generated carriers in the space‐charge region can be effectively extended by embedding a potential well on the shoulder of Schottky energy barrier. It permits the nonlinear interaction of photocurrents stimulated by spatiotemporal optical signals, which is necessary for in‐sensor reservoir computing (RC). The machine vision with the sensor reservoir constituted by designed self‐powered Au/P(VDF‐TrFE)/Cs2AgBiBr6/ITO devices is competent for both static and dynamic vision tasks. It shows an accuracy of 99.97% for face classification and 100% for dynamic vehicle flow recognition. The in‐sensor RC system takes advantage of near‐zero energy consumption in the reservoir, resulting in decades‐time lower training costs than a conventional neural network. This work paves the way for ultralow‐power machine vision using photonic devices.